HERZOG, T. Frontiers of possession: Spain and Portugal in Europe and the Americas. Cambridge: Harvard University Press, 2015 - Lopes, Jonathan Felix Ribeiro (Revista Territórios e Fronteiras, 2016)
Resenha do livro Frontiers of possession: Spain and Portugal in Europe and the Americas (2015), de Tamar Herzog.